Zeros of classical orthogonal polynomials of a discrete variable - Area, Ivan; Dimitrov, Dimitar K. [UNESP]; Godoy, Eduardo; Paschoa, Vanessa G. (Amer Mathematical Soc, 2013)
In this paper we obtain sharp bounds for the zeros of classical orthogonal polynomials of a discrete variable, considered as functions of a parameter, by using a theorem of A. Markov and the so-called Hellmann-Feynman theorem. Comparisons with previous results for zeros of Hahn, Meixner, Kravchuk and Charlier polynomials are also presented.
Keywords: Orthogonal polynomials of a discrete variable; Zeros; Charlier polynomials; Kravchuk polynomials; Meixner polynomials; Hahn polynomials; Gram polynomials